2019
DOI: 10.4103/jomfp.jomfp_83_19
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase in saliva: An assistant marker for oral squamous cell carcinoma

Abstract: Introduction: Telomerase is a ribonucleoprotein complex responsible for de novo telomere synthesis and addition of telomeric repeats to existing telomeres. Telomerase activity is generally found to be absent in normal tissues. Telomerase is known to be induced upon malignant transformation of human cells. Method: In the present study, we analyzed both telomere length and telomerase activity in saliva samples from oral carcinoma patients. The study was done to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Studies in the past show the association of genetic risk factors with malignancy, thus suggesting that genomic modifications play a significant role in the etiology of precancerous and cancerous lesions (17,18). The process of oral carcinogenesis is an exceedingly intricate and multifaceted trajectory comprising of genetic modifications accretion and, with the help of oncogenes, causes induction of proteins resulting in abnormal cell growth, augmented enzymatic (telomerase) activity encouraging cell proliferation and loss of proteins that can also inhibit the abnormal cell proliferation with the help of tumor suppressor genes (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the past show the association of genetic risk factors with malignancy, thus suggesting that genomic modifications play a significant role in the etiology of precancerous and cancerous lesions (17,18). The process of oral carcinogenesis is an exceedingly intricate and multifaceted trajectory comprising of genetic modifications accretion and, with the help of oncogenes, causes induction of proteins resulting in abnormal cell growth, augmented enzymatic (telomerase) activity encouraging cell proliferation and loss of proteins that can also inhibit the abnormal cell proliferation with the help of tumor suppressor genes (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) constitutes the majority (>90%) of oral cancers. Evidence has suggested that OSCC may Pharmaceutics 2021, 13, 574 2 of 21 have developed from precancerous lesions, such as leukoplakia and lichen planus [2]. Current oral cancer treatment modalities include surgery, radiation, and chemotherapy, depending on tumor location and stage [3].…”
Section: Introductionmentioning
confidence: 99%